Relationship between renal dysfunction and electrolyte abnormalities in hematopoietic stem cell transplant patients treated with foscarnet. (24th November 2021) - Ota, Ryosuke; Hirata, Atsushi
Abstract : This study aimed to investigate the relationship between renal dysfunction and electrolyte abnormalities, which are adverse events of foscarnet used for cytomegalovirus infection. Of the Ninety hematopoietic stem cell transplantation patients, 32 who met the selection criteria were enrolled in this retrospective study. The study patients were divided into two groups according to whether they developed renal dysfunction. The incidences of hypocalcemia, hypokalemia, and hypomagnesemia with an increase of grade 2 or higher in the renal dysfunction group were 45.5%, 18.2%, and 27.3%, respectively. Additionally, in the renal dysfunction group, a significant correlation was observed between creatinine and calcium (r = −0.458, p = 0.0244) and between creatinine and potassium (r = −0.520, p = 0.0092). This study shows that renal dysfunction and electrolyte abnormalities may be closely related in HSCT patients receiving foscarnet; thus, it is a report that may contribute to the safety of continuous foscarnet treatment.